PSWF signal based continuous phase modulation and its spectrum performance analysis - Dawei YANG; Chuanhui LIU; Jiafang KANG (Dianxin kexue)
Prolate spheroidal wave function (PSWF) signals are the best energy-gathering signals in the time-frequency domain,here is an exploratory application of PSWF signals to continuous phase modulation technology.Firstly,the process of generating CPM modulated signals based on PSWF signals was described.Secondly,a calculation method for the power spectral density of CPM modulated signals based on PSWF using the autocorrelation function method was given.Finally,combined with numerical calculation and analysis,the power spectral density and signal occupied bandwidth characteristics of minimum frequency shift keying,sinusoidal frequency shift keying,Gaussian filtered minimum shift keying and CPM modulation signal based on Gaussian function were compared.Numerical calculation results show that the PSWF signal can obtain CPM modulation signal with better spectral performance and energy concentration,compared with rectangular pulse,raised cosine pulse,Gaussian pulse and Gauss-like pulse as the baseband frequency modulation signal of CPM.